A Core Design Study for a Small Modular Boiling Water Reactor with Long-Life Core. (1st March 2016) - Wu, Zeyun; Yang, Won Sik; Shi, Shanbin; Ishii, Mamoru
Abstract: This paper presents the core design and performance characteristics of the Novel Modular Reactor (NMR-50), a 50-MW(electric) small modular reactor. NMR-50 is a boiling water reactor with natural-circulation cooling and two layers of passive safety systems that enable the reactor to withstand prolonged station blackout and loss of ultimate heat sink accidents. The main goal in the core design is to achieve a long-life core ( 10 years) without refueling for deployment in remote sites. Through assembly design studies with the CASMO-4 lattice code and coupled neutronics and thermal-hydraulic core analyses with the PARCS and RELAP5 codes, a preliminary NMR-50 core design has been developed to meet the 10-year cycle length with an average fuel enrichment of 4.75 wt% and a maximum enrichment of 5.0 wt%. The calculated fuel temperature coefficient and coolant void coefficient provide adequate negative reactivity feedbacks. The maximum fuel linear power density throughout the 10-year burn cycle is 18.7 kW/m, and the minimum critical power ratio is 2.07, both of which meet the selected design limits with significant margins. Preliminary safety analyses using the RELAP5 code show that the core will remain covered during the entire transient procedure of two design-basis loss-of-coolant accidents. These results indicate that the targeted 10-year cycle length is achievable while satisfying the operation and safety-related design criteria with sufficient margins.